Perancangan Aplikasi E-Cuti Karyawan Berbasis Web di Daehsan Indonesia Cabang Medan Menggunakan Metode Object Oriented Analysis and Design (OOAD) - Siska Ade Putry; Satriandi Satriandi; Hendra Hendra (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to analyze the effect of product quality, service quality, and customer satisfaction on customer loyalty at Njajan.co in Tegal City. This research employs a quantitative approach using a survey method involving 100 respondents who are Njajan.co customers, selected through a simple random sampling technique. Data were collected using structured questionnaires and analyzed using multiple linear regression with SPSS software. The results indicate that product quality, service quality, and customer satisfaction have a positive and significant effect on customer loyalty, both partially and simultaneously. The coefficient of determination (R²) value of 0.821 shows that 82.1% of customer loyalty variation can be explained by these three variables, while the remaining 17.9% is influenced by other factors beyond the scope of this study. These findings highlight the importance of maintaining product quality, improving service performance, and ensuring customer satisfaction as key strategies to enhance customer loyalty and strengthen business competitiveness.